PENGOLAHAN CITRA SATELIT ALOS PALSAR MENGGUNAKAN METODE POLARIMETRI UNTUK KLASIFIKASI LAHAN WILAYAH KOTA PADANG - Farah Sarjani; Josaphat Tetuko Sri Sumantyo; Yohandri Yohandri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2017)
The image processing of Alos PalSAR satellite data level 1.1 for land classification in Padang City is described in this work. The full polarimetry method is adopted in classification process which can receive and process all combinations of the four polarizations of HH, HV, VH, and VV. Yamaguchi Decomposition is applied in polarimetry method and four classification objects are obtained. Based on the modification of class simplification, the surface scattering is presented in blue color which generally describes the waters on the surface of the earth, green color for volumetric scattering, which describes about plants and forest, red or pink for the double bounce scattering depicting the settlement, urban and building and yellow for helix scattering which is the same as double bounce but the helix will more clearly identify the plant-covered settlements.